Higher Expression of DNA (de)methylation-Related Genes Reduces Adipogenicity in Dental Pulp Stem Cells - Argaez-Sosa, Adaylu A.; Rodas-Junco, Beatriz A.; Carrillo-Cocom, Leydi M.; Rojas-Herrera, Rafael A.; Coral-Sosa, Abel; Aguilar-Ayala, Fernando J.; Aguilar-Pérez, David; Nic-Can, Geovanny I. (Frontiers in Cell and Developmental Biology, 2022)
Obesity is a significant health concern that has reached alarming proportions worldwide. The overconsumption of high-energy foods might both disbalance metabolism and shoot the increase and the generation of new adipocytes by contributing to several obesity-related diseases. Such concerns demand a deeper understanding of adipocyte origin if we want to create future therapeutic applications. Recent findings indicate that adipocyte development is facilitated by tight epigenetic reprogramming, which is required to activate the gene program to change the fate of mesenchymal stem cells (MSCs) into a mature adipocyte phenotype. Because MSCs from different depots other than adipose tissue are also a potential source of adipocyte generation, it is interesting to explore whether epigenetic mechanisms of adipogenic differentiation vary from one depot to another. To investigate how DNA methylation (an epigenetic mark that plays an essential role in controlling transcription and cellular differentiation) contributes to adipogenic potential, dental pulp stem cells (DPSCs), and periodontal ligament stem cells (PLSCs) were analyzed during adipogenic differentiation in vitro. Here, we show that the differentiation capacity for the conversion of DPSCs and PLSCs to adipocytes might be associated with the pattern expression of DNA methylation-related genes acquired during the induction of the adipogenic program. Our study provides insights into the particularities of DNA methylation during the adipogenic determination of dental stem cells, which can be a starting point to identify factors that affect differentiation and provide new strategies to regulate differentiation and adipocyte expansion.